Prevalence and Risk Factors of Hypertension Among School Going Children of Dhaka City - Rahman, AFM Mizanur; Afroze, Ainun; Islam, MN (Bangladesh Journal of Child Health, 2010)
Despite general belief that hypertension is a disease of adulthood, children and adolescents can also suffer from the condition and may remain unnoticed because of lack of routine measurement of blood pressure. Hypertension in children in Bangladesh has not been well studied. Hence a study was conducted among 6-16 year-old school children of Dhaka city to find out the pattern of blood pressure (BP), prevalence of hypertension and its risk factors in this age group. In this cross sectional study, 1995 apparently healthy children of specified age group were systematically sampled from 6 purposively selected schools in Dhaka city. Their BP were measured methodically under ideal situation. On the same day, their anthropometry were also done by taking height and weight. All of them were given a questionnaire to take home for filling up the family history of hypertension, education, occupation and monthly income of their parents. Those who had BP above 95th centile on three occasions with an interval of two weeks, were diagnosed as hypertensive. Among the 1995 children, male female ratio was 1:1. There were 127-238 children in each single-year age category. Most of their fathers were service holders with 10-14 years of education. Mean systolic BP (SBP) ranged from 88.6 to 113.5 mm Hg, and mean diastolic BP (DBP) from 55.3 to 74.2 mm Hg. Girls had both SBP and DBP more than boys of same age category. Both SBP and DPB have linear relationship with age. There was significant increment in both the systolic and diastolic BP among the female children from 9 to 10 years of age. Similar sudden increment of only systolic blood pressure was seen from 13 to 14 year old male children. This study showed that prevalence of hypertension in school going children of Dhaka city was 0.55% and there was a significant relationship of hypertension with the obesity and family history of hypertension. Among the 11 hypertensive children, 9 (81.8%) had either of the two risk factors, odds ratio (95% CI) being 15.37 (3.31 - 71.37). Key words: Hypertension; school going children. DOI: 10.3329/bjch.v29i3.6184 Bangladesh J Child Health 2005; Vol 29 (3): 82-87